A kind of carboxylated styrene butadiene latex, preparation method and application thereof
By increasing the carboxyl content and polarity of carboxylic styrene butadiene latex in textile coating glue, the problem of insufficient bond fastness and water washing resistance of existing coating glue is solved, and higher bond strength and longer service life are achieved.
Patent Information
- Application Number
- CN202211676740.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2042-12-26
AI Technical Summary
The existing textile coating glue has low bond fastness, poor washing resistance and short service life, which limits its application scenarios.
Develop a carboxylic styrene butadiene latex to improve the carboxylic content and polarity of the surface of latex particles through specific formula design and preparation methods, enhance bonding fastness and water washing resistance.
It achieves high bonding fastness and good water washing resistance, extends the service life of the fabric and enhances its commercial value.
Smart Images

Figure BDA0004018536780000091 
Figure BDA0004018536780000092 
Figure BDA0004018536780000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of styrene butadiene latex synthesis, and in particular to a carboxylated styrene butadiene latex, a preparation method thereof and an application thereof. Background Art
[0002] Textile coating adhesive is a special adhesive, which is generally copolymerized by two or more monomers. After being coated on the fabric, it forms one or more layers of film on the surface of the fabric through bonding, thus achieving a printing-like effect and / or giving the fabric certain functionality. According to the characteristics of the coating adhesive, the fabric can be given a variety of functionalities such as water resistance, waterproofness, high hardness, flame retardancy and breathability. At present, in the textile field, there are three types of coating adhesives with waterproof function, namely polyacrylate coating adhesive, polyurethane coating adhesive and styrene-butadiene latex.
[0003] Polyacrylate (PA) coating adhesive is a coating agent widely used by domestic coating manufacturers. Its coating adhesive has the advantages of aging resistance, high bonding strength, and excellent water washability. Taking application number CN101864024 as an example, the application discloses a polyacrylate coating adhesive latex and a preparation method thereof, which is obtained by emulsion polymerization of soft monomers, hard monomers, cross-linking monomers, carboxyl-containing monomers, initiators, and emulsifiers, and can be applied to coating of umbrella fabrics, tents, and clothing outerwear fabrics. However, the application of polyacrylate coating is greatly limited due to its material properties of "hot sticky and cold brittle", as well as its low water pressure resistance and poor cold resistance.
[0004] In addition to water-based polyacrylate, polyurethane (PU) is also a widely used coating adhesive. Polyurethane has the advantages of strong adhesion, aging resistance, scrub resistance, and high and low temperature adaptability, but most of them are solvent-based coating agents. During processing, a large amount of organic solvents are used, which produces a lot of volatile organic compounds (VOCs), which are seriously harmful to human health and the natural environment, and the cost is also high.
[0005] Styrene butadiene latex (SBR) is the third largest coating adhesive used in the field of textiles after polyacrylate (PA) and polyurethane (PU). Styrene butadiene latex (SBR) has the advantages of low cost, good high and low temperature adaptability, and good compatibility with other additives. For example, CN108503752A discloses a styrene butadiene latex for textile coating and a preparation method thereof, which uses nano starch as a seed, butadiene and styrene as main monomers to synthesize a polymer, and uses nano hybrid silica to modify the polymer. The obtained textile coating prepared by styrene butadiene latex has the advantages of being waterproof, flame retardant, and smooth to the touch. However, fabrics made of styrene butadiene latex usually have a short service life, are easily damaged, and have poor bonding strength compared to PA and PU, and generally have poor water washability, which limits its application scenarios.
[0006] Therefore, it is urgent to develop a textile styrene-butadiene latex with high bonding strength, good water resistance and long service life to extend the service life of the fabric and make it have better commercial value. Summary of the invention
[0007] In order to solve at least one of the above technical problems and develop a textile styrene butadiene latex with high bonding strength, good water resistance and long service life, the present application provides a carboxylated styrene butadiene latex, a preparation method and application thereof.
[0008] On the one hand, the present application provides a carboxylated styrene butadiene latex, which comprises the following components in parts by weight: 80 to 120 parts of deionized water, 50 to 60 parts of butadiene, 40 to 50 parts of styrene, 0 to 10 parts of polar monomers, 3 to 5 parts of cross-linking monomers, 2 to 5 parts of dicarboxylic unsaturated carboxylic acids, 0.6 to 1 part of initiator, 0.4 to 0.8 part of molecular weight regulator, 1 to 3 parts of emulsifier, 0.2 to 0.6 part of neutralizer, 0.1 to 0.5 part of defoaming agent, and 0.2 to 0.8 part of antioxidant.
[0009] Optionally, the carboxylated styrene-butadiene latex further comprises 0.1 to 0.8 parts of ethylenediaminetetraacetic acid sodium salt.
[0010] Further optionally, the sodium salt of EDTA is selected from one of disodium EDTA, tetrasodium EDTA and sodium ferric EDTA.
[0011] Further optionally, the raw materials of the carboxylated styrene butadiene latex include the following components by weight: 90-100 parts of deionized water, 52-57 parts of butadiene, 44-46 parts of styrene, 1-4 parts of polar monomers, 4-5 parts of cross-linking monomers, 4-5 parts of dicarboxylic unsaturated carboxylic acids, 0.7-0.9 parts of initiators, 0.5-0.7 parts of molecular weight regulators, 2-3 parts of emulsifiers, 0.5-0.6 parts of neutralizers, 0.1-0.3 parts of defoaming agents, 0.3-0.8 parts of antioxidants, and 0.1-0.5 parts of sodium salt of ethylenediaminetetraacetic acid.
[0012] Optionally, the polar monomer is selected from one or a combination of more than one of butyl acrylate, acrylonitrile, methyl methacrylate and ethyl acrylate.
[0013] Optionally, the cross-linking monomer is selected from one or a combination of hydroxyethyl acrylate, hydroxypropyl acrylate, acrylamide, and diacetone acrylamide.
[0014] Optionally, the dicarboxylic unsaturated carboxylic acid is selected from one or a combination of more than one of fumaric acid, itaconic acid and maleic acid.
[0015] Optionally, the initiator is selected from one or a combination of potassium persulfate, ammonium persulfate, sodium persulfate.
[0016] Optionally, the molecular weight regulator is selected from one or a combination of tert-dodecyl mercaptan, butyl 3-mercaptopropionate, isooctyl 3-mercaptopropionate, and ethyl 3-mercaptobutyrate.
[0017] Optionally, the emulsifier is selected from one or a combination of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl diphenyl ether disulfonate, and sodium salt of dicyclohexyl sulfonated succinate.
[0018] Optionally, the neutralizing agent is selected from one or a combination of more than one of sodium bicarbonate, ammonium bicarbonate, ammonia water, sodium hydroxide and potassium hydroxide.
[0019] In a second aspect, the present application provides a method for preparing the above-mentioned carboxylated styrene butadiene latex, comprising the following steps:
[0020] S1. Preparation of aqueous primer: 50-60% of deionized water, 8-15% of emulsifier, 15-25% of unsaturated dicarboxylic acid, 4-8% of cross-linking monomer, and sodium salt of ethylenediaminetetraacetic acid and neutralizer are stirred and dissolved to mix evenly;
[0021] S2, water phase drop material preparation: the remaining amount of deionized water, emulsifier, and 55-65% of the unsaturated dicarboxylic acid are stirred and dissolved and mixed evenly;
[0022] S3, under vacuum conditions, all the aqueous phase primer prepared in step S1, 4-8% styrene, and the molecular weight regulator and butadiene in the formula are mixed, the temperature is raised to 75-80° C., 25-35% initiator in the formula is added, the temperature is continued to be raised to 84-88° C., heating is stopped, and then the temperature is controlled at 92-95° C., and the reaction is carried out for 10-30 minutes;
[0023] S4, during the temperature control reaction in step S3, the aqueous phase drop material prepared in step S2 and the remaining amount of styrene, molecular weight regulator and butadiene are simultaneously added to the reaction solution of the temperature control reaction in step S3, and the temperature is continuously controlled to be maintained at 92-95° C., and the reaction is continued; sampling and monitoring are performed during the reaction, and when the sampled solid content reaches 70-75% of the theoretical solid content, the drop addition of the aqueous phase drop material is suspended, and the remaining amount of the aqueous solution of the unsaturated dicarboxylic acid monomer is added, and stirred for 10-12 minutes, and then the remaining aqueous phase drop material is continued to be added until the drop addition is completed, and the drop addition time is controlled to be 3-5 hours;
[0024] S5, heating the reaction solution of step S4 to 95-98° C., keeping the temperature for 1-2 hours, adjusting the pH value of the reaction solution, and then adding a formulated amount of defoaming agent for degassing;
[0025] S6, monitoring the VOC value of the reaction solution in step S5, when the VOC value of the reaction solution drops below 200 ppm, cooling the reaction solution to below 45°C, then adding a formulated amount of antioxidant, and then adjusting the pH value of the reaction solution again, filtering the discharged material, and obtaining carboxylated styrene butadiene latex.
[0026] Optionally, in S3, the vacuum degree of the vacuum condition is set below -0.085Mpa.
[0027] Optionally, in S5, the pH value of the reaction solution is adjusted to 5-6.
[0028] Optionally, in S6, the pH value of the reaction solution is adjusted to 6.5-7.5.
[0029] Optionally, in S6, the filtration is performed using a sieve filtration having a mesh size of 150 to 300.
[0030] In a third aspect, the present application also protects the application of the above-mentioned carboxylated styrene butadiene latex in the field of textile coatings and / or textile finishing agents.
[0031] In summary, the present invention includes at least one of the following beneficial technical effects:
[0032] 1. The dicarboxyl monomer used in the formula of the present application has two carboxyl groups, which have large steric hindrance. During emulsion polymerization, it tends to stay on the surface of the latex particles. The carboxyl groups staying on the surface of the latex particles are more likely to undergo cross-linking reactions with the cross-linking groups carried by other latex particles, thereby improving the overall strength of the coating and then improving the water washability of the system.
[0033] 2. When the carboxylated styrene butadiene latex prepared in the present application is used as a textile coating adhesive, more carboxyl groups are distributed on the surface of the latex particles, the polarity is stronger, and the interaction with the textile fiber molecules is stronger, thereby improving the bonding strength of the carboxylated styrene butadiene latex.
[0034] 3. In the method of the present application, when the solid content in the dropping stage reaches 70-75% of the theoretical solid content, the remaining 20% of the dicarboxyl monomer is added in a concentrated manner, so that the carboxyl groups are distributed more on the surface of the latex particles and relatively less inside the latex particles, thereby further improving the overall strength of the coating and further improving the water wash resistance.
[0035] 4. The present application does not use expensive reactive emulsifiers and special emulsifiers, and uses less polar monomers or no polar monomers, thereby reducing the cost of the entire preparation process; at the same time, the coating agent prepared by the present application does not contain harmful substances such as formaldehyde, and the product is more environmentally friendly. Overall, it is very economical. DETAILED DESCRIPTION
[0036] The present application is further described in detail below with reference to the embodiments.
[0037] The present application designs a carboxylated styrene-butadiene latex, which comprises the following components, measured by weight: 80 to 120 parts of deionized water, 50 to 60 parts of butadiene, 40 to 50 parts of styrene, 0 to 10 parts of polar monomers, 3 to 5 parts of cross-linking monomers, 2 to 5 parts of dicarboxylic unsaturated carboxylic acids, 0.6 to 1 part of initiator, 0.4 to 0.8 part of molecular weight regulator, 1 to 3 parts of emulsifier, 0.2 to 0.6 part of neutralizer, 0.1 to 0.5 part of defoaming agent, and 0.2 to 0.8 part of antioxidant.
[0038] The present application provides a method for preparing carboxylated styrene butadiene latex, comprising the following steps:
[0039] S1. Preparation of aqueous primer: 50-60% of deionized water, 8-15% of emulsifier, 15-25% of unsaturated dicarboxylic acid, 4-8% of cross-linking monomer, and sodium salt of ethylenediaminetetraacetic acid and neutralizer are stirred and dissolved to mix evenly;
[0040] S2, water phase drop material preparation: the remaining amount of deionized water, emulsifier, and 55-65% of the unsaturated dicarboxylic acid are stirred and dissolved and mixed evenly;
[0041] S3, under vacuum conditions, all the aqueous phase primer prepared in step S1, 4-8% styrene, and the molecular weight regulator and butadiene in the formula are mixed, the temperature is raised to 75-80° C., 25-35% initiator in the formula is added, the temperature is continued to be raised to 84-88° C., heating is stopped, and then the temperature is controlled at 92-95° C., and the reaction is carried out for 10-30 minutes;
[0042] S4, during the temperature control reaction in step S3, the aqueous phase drop material prepared in step S2 and the remaining amount of styrene, molecular weight regulator and butadiene are simultaneously added to the reaction solution of the temperature control reaction in step S3, and the temperature is continuously controlled to be maintained at 92-95° C., and the reaction is continued; sampling and monitoring are performed during the reaction, and when the sampled solid content reaches 70-75% of the theoretical solid content, the drop addition of the aqueous phase drop material is suspended, and the remaining amount of the aqueous solution of the unsaturated dicarboxylic acid monomer is added, and stirred for 10-12 minutes, and then the remaining aqueous phase drop material is continued to be added until the drop addition is completed, and the drop addition time is controlled to be 3-5 hours;
[0043] S5, heating the reaction solution of step S4 to 95-98° C., keeping the temperature for 1-2 hours, adjusting the pH value of the reaction solution, and then adding a formulated amount of defoaming agent for degassing;
[0044] S6, monitoring the VOC value of the reaction solution in step S5, when the VOC value of the reaction solution drops below 200 ppm, cooling the reaction solution to below 45°C, then adding a formulated amount of antioxidant, and then adjusting the pH value of the reaction solution again, filtering the discharged material, and obtaining carboxylated styrene butadiene latex.
[0045] Before this application, the styrene butadiene latex sold on the market had poor heat and salt resistance, dispersibility, and toughening ability, and was still not ideal in terms of water resistance, and the cost was high. When the existing styrene butadiene latex was modified, most of them used nano starch and nano inorganic fillers to modify the styrene butadiene latex by co-polymerization of butadiene and styrene to reduce costs and improve functionality. Its modification method has been widely used, but the prepared styrene butadiene latex is no longer suitable for the higher performance requirements of styrene butadiene latex today.
[0046] The inventors of the present application have found in practice that, for textile coatings, the modification of styrene-butadiene latex with nano-starch and inorganic fillers will bring new technical problems. Although the styrene-butadiene latex modified with nano-starch and inorganic fillers can improve the functionality such as gas barrier, flame retardancy, water resistance, and smooth feel, if the dispersibility of the inorganic filler is insufficient, it will seriously affect the stability of the latex. At the same time, the bonding strength of the above-mentioned modified latex is low, and the water washability is generally poor. The fabrics obtained usually have a short service life and the fabrics are easily damaged, resulting in limited application scenarios. The above-mentioned technical problems have not been reported in the prior art before the present application.
[0047] The inventors of the present application have designed the technical solution of the present application in view of the above-mentioned new technical problems. Through a special formula design and a corresponding preparation method, the carboxylated styrene butadiene latex of the present application is prepared, which not only has extremely strong bonding fastness and coating strength, but also has low cost and good water washability. It has great economic benefits and can effectively solve the above-mentioned technical problems.
[0048] The design of this application fully considers the improvement of water-washing resistance and coating strength, while taking into account the bonding strength. When designing this application, the aqueous phase primer and aqueous phase dripping material are first prepared. The prepared aqueous phase primer is not easily affected by the change of pH value of the environment and changes in viscosity within a certain pH range of the environment, and has good dispersibility in the aqueous phase system in which it is located. In addition, this application introduces dicarboxyl unsaturated carboxylic acid into the ingredients. The dicarboxyl monomer used has two carboxyl groups and has a large steric hindrance. During emulsion polymerization, the carboxyl groups remaining on the surface of the latex particles are more likely to undergo cross-linking reactions with the cross-linking groups carried by other latex particles, thereby improving the overall strength of the coating and then improving the water-washing resistance of the system.
[0049] Secondly, in order to further improve the water resistance and the bonding strength, the present application concentrates on dripping the remaining dicarboxyl monomer when the solid content in the dripping section reaches 70-75% of the theoretical solid content, so that the carboxyl groups are distributed more on the surface of the latex particles and relatively less inside. When the carboxyl styrene butadiene latex prepared by the method is used as a textile coating, because the latex particles have more carboxyl groups on the surface, the polarity is stronger, and the interaction with the textile fiber molecules is stronger, thereby being able to improve the bonding strength of the carboxyl styrene butadiene latex as a whole.
[0050] Finally, the present application fully considered the cost and environmental protection issues when designing the above compounding system, and therefore chose the above design, which does not use expensive reactive emulsifiers and special emulsifiers, uses less polar monomers or does not use polar monomers, thereby reducing the cost of the entire preparation process. In addition, the coating agent prepared by the present application does not contain harmful substances such as formaldehyde, and the product is more environmentally friendly. Overall, it is very economical.
[0051] The following are preparation examples and embodiments of the present application.
[0052] Preparation Example
[0053] The following preparation examples differ in that: the raw material composition of each component. The following raw materials have no special source description and are all commercially available conventional materials.
[0054] Preparation Examples 1 to 7 provide a polar monomer, which includes the following components by weight percentage:
[0055] Preparation Example 1
[0056] A polar monomer consisting of 100% by weight butyl acrylate.
[0057] Preparation Example 2
[0058] A polar monomer consisting of 100% by weight acrylonitrile.
[0059] Preparation Example 3
[0060] A polar monomer consisting of 100%wt methyl methacrylate.
[0061] Preparation Example 4
[0062] A polar monomer consisting of 100% by weight ethyl acrylate.
[0063] Preparation Example 5
[0064] A polar monomer consists of 50% by weight of butyl acrylate and 50% by weight of acrylonitrile.
[0065] Preparation Example 6
[0066] A polar monomer consists of 70% by weight of methyl methacrylate and 30% by weight of ethyl acrylate.
[0067] Preparation Example 7
[0068] A polar monomer consists of 20% wt of butyl acrylate, 40% wt of acrylonitrile, 30% wt of methyl methacrylate and 10% wt of ethyl acrylate.
[0069] Preparation Examples 8 to 12 provide a cross-linking monomer, which includes the following components by weight percentage:
[0070] Preparation Example 8
[0071] A crosslinking monomer consisting of 100% by weight hydroxyethyl acrylate.
[0072] Preparation Example 9
[0073] A cross-linking monomer consists of 40% by weight of hydroxyethyl acrylate and 60% by weight of hydroxypropyl acrylate.
[0074] Preparation Example 10
[0075] A cross-linking monomer consists of 20% wt of hydroxypropyl acrylate, 40% wt of acrylamide and 40% wt of diacetone acrylamide.
[0076] Preparation Example 11
[0077] A cross-linking monomer consists of 100% by weight of diacetone acrylamide.
[0078] Preparation Example 12
[0079] A cross-linking monomer consists of 10% wt of hydroxyethyl acrylate, 40% wt of hydroxypropyl acrylate, 20% wt of acrylamide and 30% wt of diacetone acrylamide.
[0080] Preparation Examples 13 to 18 provide a dicarboxylic unsaturated carboxylic acid, comprising the following components by weight percentage:
[0081] Preparation Example 13
[0082] A dicarboxylic unsaturated carboxylic acid consisting of 100% by weight fumaric acid.
[0083] Preparation Example 14
[0084] A dicarboxylic unsaturated carboxylic acid, consisting of 100% by weight of itaconic acid.
[0085] Preparation Example 15
[0086] A dicarboxylic unsaturated carboxylic acid consisting of 100% by weight of maleic acid.
[0087] Preparation Example 16
[0088] A dicarboxylic unsaturated carboxylic acid consists of 50%wt of fumaric acid and 50%wt of itaconic acid.
[0089] Preparation Example 17
[0090] A dicarboxyl unsaturated carboxylic acid consists of 30%wt of fumaric acid and 70%wt of maleic acid.
[0091] Preparation Example 18
[0092] A dicarboxyl unsaturated carboxylic acid consists of 20%wt of fumaric acid, 30%wt of itaconic acid and 50%wt of maleic acid.
[0093] Preparation Examples 19 to 21 provide an initiator comprising the following components by weight percentage:
[0094] Preparation Example 19
[0095] An initiator consists of 100%wt sodium persulfate.
[0096] Preparation Example 20
[0097] An initiator consists of 50%wt sodium persulfate and 50%wt ammonium persulfate.
[0098] Preparation Example 21
[0099] An initiator consists of 100%wt potassium persulfate.
[0100] Preparation Examples 22 to 25 provide a molecular weight regulator, which includes the following components by weight percentage:
[0101] Preparation Example 22
[0102] A molecular weight regulator consists of 100% by weight of tert-dodecyl mercaptan.
[0103] Preparation Example 23
[0104] A molecular weight regulator is composed of 50% by weight of tert-dodecyl mercaptan and 50% by weight of isooctyl 3-mercaptopropionate.
[0105] Preparation Example 24
[0106] A molecular weight regulator is composed of 20% wt of tert-dodecyl mercaptan, 30% wt of butyl 3-mercaptopropionate and 50% wt of ethyl 3-mercaptobutyrate.
[0107] Preparation Example 25
[0108] A molecular weight regulator consists of 100% by weight of ethyl 3-mercaptobutyrate.
[0109] Preparation Examples 26 to 29 provide an emulsifier comprising the following components by weight percentage:
[0110] Preparation Example 26
[0111] An emulsifier consists of 100%wt of sodium lauryl sulfate.
[0112] Preparation Example 27
[0113] An emulsifier consists of 50%wt of sodium dodecyl sulfate and 50%wt of sodium dodecylbenzene sulfonate.
[0114] Preparation Example 28
[0115] An emulsifier consists of 100% by weight of sodium dodecyl diphenyl ether disulfonate.
[0116] Preparation Example 29
[0117] An emulsifier consists of 100%wt of sodium salt of dicyclohexyl sulfonated succinate.
[0118] Preparation Examples 30 to 33 provide a neutralizing agent, which comprises the following components by weight percentage:
[0119] Preparation Example 30
[0120] A neutralizing agent consists of 50%wt of sodium bicarbonate and 50%wt of ammonium bicarbonate.
[0121] Preparation Example 31
[0122] A neutralizing agent consists of 100%wt ammonium bicarbonate.
[0123] Preparation Example 32
[0124] A neutralizing agent consists of 100%wt ammonia water.
[0125] Preparation Example 33
[0126] A neutralizing agent consists of 50%wt of sodium hydroxide and 50%wt of potassium hydroxide.
[0127] Example
[0128] The sodium salt of ethylenediaminetetraacetic acid in Examples 1 to 7 is ethylenediaminetetraacetic acid disodium produced by Sigma-Aldrich, the defoaming agent is Tego 810 produced by Digo, and the antioxidant is BHT aqueous emulsion produced by Sigma-Aldrich; butadiene and styrene are both products produced by Shanghai Aladdin; and deionized water is self-produced deionized water.
[0129] Example 1
[0130] The styrene-butadiene latex of this embodiment includes the following raw materials in parts by weight: 80 parts of deionized water, 50 parts of butadiene, 50 parts of styrene, 2 parts of polar monomer, 3 parts of cross-linking monomer, 2 parts of dicarboxylic unsaturated carboxylic acid, 0.6 parts of initiator, 0.4 parts of molecular weight regulator, 1 part of emulsifier, 0.2 parts of neutralizer, 0.1 parts of defoaming agent, 0.2 parts of antioxidant, and 0.5 parts of disodium ethylenediaminetetraacetate.
[0131] Among them, the composition of some components and raw materials is shown in Table 1:
[0132]
[0133] The preparation method comprises the following steps:
[0134] S1. Preparation of aqueous primer: Add 55% deionized water (44 parts), 10% emulsifier (0.1 parts), 20% dicarboxyl unsaturated dicarboxylic acid (0.4 parts), 5% cross-linking monomer (0.15 parts), all disodium ethylenediaminetetraacetate (0.5 parts) and neutralizer (0.2 parts) into the aqueous phase tank, stir well to dissolve, and mix evenly;
[0135] S2, water phase drop material preparation: the remaining deionized water, emulsifier, 60% dicarboxylic unsaturated dicarboxylic acid (1.2 parts), fully stirred to dissolve, mix evenly;
[0136] S3, after the reactor is evacuated, add all the water phase primer, 5% styrene (2.5 parts), molecular weight regulator (0.02 parts), butadiene (2.5 parts), heat to 75-80°C, add 30% initiator (0.18 parts), continue to heat to 85°C, stop heating, control the temperature at 92°C, and react for 25 minutes;
[0137] S4, at the reaction temperature of step S3, simultaneously start to drop the water phase addition material, the remaining styrene, molecular weight regulator, butadiene, when the sample solid content reaches 70% of the theoretical solid content, stop dropping, add the remaining 20% aqueous solution of unsaturated dicarboxylic acid monomer (0.4 parts) into the water phase tank, stir for 10 minutes, continue to drop until the drop addition is completed, and control the time for the end of the drop addition to be 3.5 hours;
[0138] S5, heating to 95°C, keeping warm for 1.5 hours, transferring the reaction solution into a degassing kettle, adjusting the pH value to 5 with liquid alkali, and adding a defoaming agent for degassing;
[0139] S6. Monitor the VOC value. When the VOC value drops below 200 ppm, cool to below 45° C., add an antioxidant, adjust the pH value to 6.5 with liquid alkali, discharge the material, filter with a 150-300 mesh sieve, and obtain carboxylated styrene butadiene latex.
[0140] Embodiments 2 to 7
[0141] Examples 2 to 7 respectively provide a carboxylated styrene butadiene latex, which differs from Example 1 in that the preparation of polar monomers is different and the weight fractions of each component are different. The polar monomers used in Examples 2 to 7 are respectively the polar monomers of Preparation Example 1, Preparation Example 2, Preparation Example 3, Preparation Example 4, Preparation Example 6 and Preparation Example 7. The specific parameter settings are shown in Table 2.
[0142] Table 2 Components and their corresponding weight parts in Examples 2-7
[0143]
[0144]
[0145] Performance testing experiment
[0146] 1. Detection object
[0147] The optimal embodiment of the invention patent with publication number CN106749917A is taken as comparative example 1, SD593 styrene butadiene latex produced by BASF specifically for fabrics is taken as comparative example 2, and the styrene butadiene latex prepared with the raw materials of Examples 1 to 7 and the styrene butadiene latex of comparative examples 1 and 2 are comprehensively tested for their performance according to the test method of this test experiment, and the test results are recorded in Table 3.
[0148] 2. Test methods
[0149] Test 1: Washability test
[0150] Take 5%wt organic pigment, 20%wt adhesive, 40%wt thickener PTF and 1%wt urea, and the rest is the test sample styrene-butadiene latex, adjust the pH value of the mixture to 7-8 with ammonia water, and stir to a certain viscosity to obtain printing paste. Then, use the warp scraping method to print the polyester plain fabric, scraping once. After pre-baking the printed fabric in an oven at 80℃ for 3min, bake it at 140℃ for 4min.
[0151] Take printing glue as an example. After printing on the fabric, wash it in a washing machine at 60℃ for 3 hours / time for multiple times. Compare it with the fabric before washing, and record the number of washes if the printing does not fall off obviously.
[0152] Test 2: pH determination
[0153] The test was carried out according to the method described in SH / T1150-1999 "Determination of pH value of synthetic rubber latex".
[0154] Test 3: Chemical stability test
[0155] The test was carried out according to the method described in SH / T1608-1995 "Determination of the stability of styrene-butadiene latex to calcium ions".
[0156] Test 4: Mechanical stability test
[0157] The sample was placed in a high-speed mixer and stirred at a speed of 2000 rpm for half an hour. The resulting product was then passed through a 300-mesh sieve and the solid product was dried. The weight ratio of the dry product to the original latex was used to measure the mechanical stability of the latex. The smaller the weight ratio, the better the mechanical stability.
[0158] Test 5: Bond strength test
[0159] Refer to the test method in GB / T 2791-1995T for testing.
[0160] Test 6: VOC value detection
[0161] The test shall be carried out in accordance with the relevant provisions and testing standards in GB 33372-2020 "Limits of Volatile Organic Compounds in Adhesives".
[0162] 3. Test results
[0163] The performance of Examples 1 to 7 was tested, and the test results are shown in Table 3.
[0164] Table 3: Performance test data record table
[0165]
[0166] 4. Result analysis:
[0167] From the results in Table 3, it can be seen that the chemical stability and mechanical stability of the styrene butadiene latex of the present application are very close to those of the existing styrene butadiene latex, and slightly better than the existing styrene butadiene latex. In terms of bonding strength and washing durability, the styrene butadiene latex of the present application is significantly better than the existing styrene butadiene latex, especially in terms of washing durability, which is more than twice that of the existing styrene butadiene latex.
[0168] It can also be seen from the results in Table 3 that the selection and dosage of carboxyl groups and the selection of cross-linking monomers have a great influence on the number of wash durability of styrene-butadiene latex.
[0169] Based on Example 3, Examples 8 to 14 were designed. The difference between Examples 8 to 14 and Example 3 is the selection and dosage of carboxyl groups. The specific settings are shown in Table 4.
[0170] Table 4: Selection and dosage of carboxyl groups
[0171]
[0172] The above performance tests were performed on Examples 8 to 14, and the test results are recorded in Table 5.
[0173] Table 5: Performance test data record table
[0174]
[0175] Result analysis:
[0176] It can be seen from the data in Table 5 that when maleic acid is used as the dicarboxyl raw material, the washing durability and bonding strength of styrene-butadiene latex will be better than those of other raw materials; and when mixed dicarboxyl raw materials are used, the washing durability and bonding strength of styrene-butadiene latex are significantly improved compared with those using a single raw material. It can be seen that the mixed dicarboxyl raw materials and multiple components can have a certain synergistic effect.
[0177] It can also be seen from the data in Table 5 that within a certain dosage range, the greater the dosage of the dicarboxyl raw material, the better the water resistance and bonding strength of the styrene-butadiene latex.
[0178] In addition, the selection of crosslinking monomers also has a certain influence on the performance of carboxylated styrene butadiene latex. Taking Example 4 as an example, Examples 15 to 21 are designed. The difference between Examples 15 to 21 and Example 4 is: the selection and dosage of the crosslinking monomers. The specific settings are shown in Table 6.
[0179] Table 6: Selection and dosage of carboxyl groups
[0180]
[0181] The above performance tests were performed on Examples 15 to 21, and the test results are recorded in Table 7.
[0182] Table 7: Performance test data record table
[0183]
[0184] Result analysis:
[0185] It can be seen from the data in Table 7 that the use of mixed cross-linking monomers can significantly improve the number of wash resistance and bonding strength of styrene-butadiene latex compared with the use of single-component cross-linking monomers. It can be seen that the mixed cross-linking monomers and multiple components can have a certain coordination effect. After cross-linking, the groups of each cross-linking monomer component can form a certain synergistic effect, making the performance of styrene-butadiene latex better.
[0186] It can also be seen from the data in Table 7 that within a certain dosage range, the greater the amount of cross-linking monomer used, the better the water resistance and bonding strength of the styrene-butadiene latex.
[0187] The present application optimizes the proportion of each component by analyzing the data in Table 3, Table 5 and Table 7. The following are Examples 22 to 28 of the present application. The polar monomer, crosslinking monomer and dicarboxyl unsaturated carboxylic acid in Examples 22 to 28 are respectively prepared in Preparation Example 5, Preparation Example 12 and Preparation Example 18, and the preparation and proportion of other components are shown in Table 8 and Table 9, respectively.
[0188] Table 8: Selection of some components of Examples 22 to 28
[0189]
[0190]
[0191] Table 9 Components and their corresponding weight parts in Examples 22-28
[0192]
[0193] The performance of Examples 22 to 28 was tested, and the test results are shown in Table 10.
[0194] Table 10: Performance test data record table of Examples 22 to 28
[0195]
[0196]
[0197] It can be seen from the data in Table 10 that the performance of the prepared styrene-butadiene latex can be further significantly improved after accurately controlling the selection and dosage of polar monomers, crosslinking monomers and dicarboxylic unsaturated carboxylic acids and optimizing the selection and dosage of other components.
[0198] Taking Example 3 as an example, comparative examples 1 to 10 are designed. Comparative examples 1 to 10 respectively provide a carboxylated styrene butadiene latex, which is different from Example 3 in that the preparation steps are different. The specific preparation steps are as follows.
[0199] Comparative Example 1
[0200] The difference from Example 3 is that the polar monomer is 16 parts.
[0201] Comparative Example 2
[0202] The difference from Example 3 is that: 1 part of dicarboxylic unsaturated carboxylic acid is used.
[0203] Comparative Example 3
[0204] The difference from Example 3 is that: 11 parts of dicarboxylic unsaturated carboxylic acid are used.
[0205] Comparative Example 4
[0206] The difference from Example 3 is that the cross-linking monomer is 2 parts.
[0207] Comparative Example 5
[0208] The difference from Example 3 is that the cross-linking monomer is 6 parts.
[0209] Comparative Example 6
[0210] The difference from Example 3 is that: S3, after the reactor is evacuated, all the water phase primer, 5% styrene, molecular weight regulator, butadiene are added, the temperature is raised to 85°C, 30% initiator is added, heating is stopped, the temperature is controlled at 92-95°C, and the reaction is carried out for 25 minutes.
[0211] Comparative Example 7
[0212] The difference from Example 3 is that: S4, at the reaction temperature of step S3, the water phase addition material, the remaining styrene, molecular weight regulator, butadiene, and the remaining 20% aqueous solution of unsaturated dicarboxylic acid monomer are added to the water phase tank, stirred for 10 minutes, and continued to drop until the addition is completed, and the time for the end of the addition is controlled to be 3.5 hours.
[0213] Comparative Example 8
[0214] The difference from Example 3 is that: S5, the temperature is raised to 95° C., and after keeping the temperature for 1.5 hours, the reaction solution is transferred to a degassing kettle, and a defoaming agent is added for degassing treatment.
[0215] Comparative Example 9
[0216] The difference from Example 3 is that: S6, after degassing, directly cool to below 45°C, add antioxidant, adjust pH to 6.5 with liquid alkali, discharge, filter with 150-300 mesh sieve, and obtain carboxylated styrene butadiene latex.
[0217] Comparative Example 10
[0218] The difference from Example 3 is: S6, monitoring the VOC value, when the VOC value drops below 200 ppm, cooling to below 45° C., adding an antioxidant, stirring the material, filtering through a 150-300 mesh sieve, and obtaining carboxylated styrene butadiene latex.
[0219] The above performance tests were performed for Comparative Examples 1 to 10, and the test results are recorded in Table 11.
[0220] Table 11: Performance test data record table
[0221]
[0222] Result analysis:
[0223] From the data in Table 11, it can be seen that the amount of dicarboxyl unsaturated carboxylic acid and cross-linking monomer has a great influence on the performance of the present invention. If the amount is too low, the bonding strength and water washing resistance of the present invention will be greatly reduced; and when the amount exceeds a certain level, there is no significant improvement in the bonding strength and water washing resistance of the present invention. When the amount of polar monomer exceeds 10 parts, the performance improvement is not obvious, but the cost will obviously increase significantly.
[0224] It can also be seen from the data in Table 11 that the control of the preparation steps of the present application also has a great influence on the performance of the styrene-butadiene latex of the present application. The control of the amount of material added, the control of the order of addition, and the control of the remaining 20% unsaturated dicarboxylic acid monomer in the process and the cooling node of the final step all have a great influence on the performance of the styrene-butadiene latex of the present application. Monitoring the solid content to reach 70-75% of the theoretical solid content, and the VOC value of the reaction solution in the monitoring step, using the above monitoring results as the control node, can ensure that the carboxyl groups are more distributed on the surface of the latex particles, and the cross-linking degree is higher, thereby further improving the overall strength of the coating and further improving the water washing resistance.
[0225] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A carboxylated styrene-butadiene latex, characterized in that: The raw materials of the carboxylated styrene butadiene latex include the following components by weight: 80-120 parts of deionized water, 50-60 parts of butadiene, 40-50 parts of styrene, 0-10 parts of polar monomers, 3-5 parts of crosslinking monomers, 2-5 parts of dicarboxyl unsaturated carboxylic acids, 0.6-1 parts of initiators, 0.4-0.8 parts of molecular weight regulators, 1-3 parts of emulsifiers, 0.2-0.6 parts of neutralizers, 0.1-0.5 parts of defoamers, and 0.2-0.8 parts of antioxidants; The polar monomer consists of butyl acrylate and acrylonitrile, the cross-linking monomer consists of hydroxyethyl acrylate, hydroxypropyl acrylate, acrylamide and diacetone acrylamide, and the dicarboxylic unsaturated carboxylic acid consists of fumaric acid, itaconic acid and maleic acid.
2. A carboxylated styrene-butadiene latex according to claim 1, characterized in that: The carboxylated styrene butadiene latex also includes 0.1 to 0.8 parts of ethylenediaminetetraacetic acid sodium salt; the ethylenediaminetetraacetic acid sodium salt is selected from one of disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, and sodium ferric ethylenediaminetetraacetate.
3. A carboxylated styrene-butadiene latex according to claim 2, characterized in that: The invention comprises the following components by weight: 90-100 parts of deionized water, 52-56 parts of butadiene, 45-48 parts of styrene, 1-4 parts of polar monomer, 4-5 parts of cross-linking monomer, 4-5 parts of dicarboxyl unsaturated carboxylic acid, 0.7-0.9 parts of initiator, 0.5-0.7 parts of molecular weight regulator, 2-3 parts of emulsifier, 0.5-0.6 parts of neutralizer, 0.1-0.3 parts of defoamer, 0.3-0.8 parts of antioxidant and 0.1-0.5 parts of sodium salt of ethylenediaminetetraacetic acid.
4. A carboxylated styrene-butadiene latex according to claim 1, characterized in that: The initiator is selected from one or more combinations of potassium persulfate, ammonium persulfate, and sodium persulfate; the molecular weight regulator is selected from one or more combinations of tert-dodecyl mercaptan, butyl 3-mercaptopropionate, isooctyl 3-mercaptopropionate, and ethyl 3-mercaptobutyrate; the emulsifier is selected from one or more combinations of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium dodecyl diphenyl ether disulfonate, and sodium salt of dicyclohexyl sulfonated succinate; the neutralizer is selected from one or more combinations of sodium bicarbonate, ammonium bicarbonate, ammonia water, sodium hydroxide, and potassium hydroxide.
5. A method for preparing carboxylated styrene butadiene latex as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Preparation of aqueous primer: 50-60% of deionized water, 8-15% of emulsifier, 15-25% of unsaturated dicarboxylic acid, 4-8% of cross-linking monomer, and sodium salt of ethylenediaminetetraacetic acid and neutralizer are stirred and dissolved to mix evenly; S2, water phase drop material preparation: the remaining amount of deionized water, emulsifier, and 55-65% of the unsaturated dicarboxylic acid are stirred and dissolved and mixed evenly; S3, under vacuum conditions, all the aqueous phase primer prepared in step S1, 4-8% styrene, and the molecular weight regulator and butadiene in the formula are mixed, the temperature is raised to 75-80° C., 25-35% initiator in the formula is added, the temperature is continued to be raised to 84-88° C., heating is stopped, and then the temperature is controlled at 92-95° C., and the reaction is carried out for 10-30 minutes; S4, during the temperature control reaction in step S3, the aqueous phase drop material prepared in step S2 and the remaining amount of styrene, molecular weight regulator and butadiene are simultaneously added to the reaction solution of the temperature control reaction in step S3, and the temperature is continuously controlled to be maintained at 92-95° C., and the reaction is continued; sampling and monitoring are performed during the reaction, and when the sampled solid content reaches 70-75% of the theoretical solid content, the drop addition of the aqueous phase drop material is suspended, and the remaining amount of the aqueous solution of the unsaturated dicarboxylic acid monomer is added, and stirred for 10-12 minutes, and then the remaining aqueous phase drop material is continued to be added until the drop addition is completed, and the drop addition time is controlled to be 3-5 hours; S5, heating the reaction solution of step S4 to 95-98° C., keeping the temperature for 1-2 hours, adjusting the pH value of the reaction solution, and then adding a formulated amount of defoaming agent for degassing; S6, monitoring the VOC value of the reaction solution in step S5, when the VOC value of the reaction solution drops below 200 ppm, cooling the reaction solution to below 45°C, then adding a formulated amount of antioxidant, and then adjusting the pH value of the reaction solution again, filtering the discharged material, and obtaining carboxylated styrene butadiene latex.
6. The method for preparing carboxylated styrene butadiene latex according to claim 5, characterized in that: In S3, the vacuum degree of the vacuum condition is set below -0.085Mpa; in S5, the pH value of the reaction liquid is adjusted to 5-6, and in S6, the pH value of the reaction liquid is adjusted to 6.5-7.5; in S6, the filtration is performed by sieve filtration, and the mesh number of the sieve is 150-300 meshes.
7. Use of the carboxylated styrene butadiene latex as claimed in any one of claims 1 to 4 in the field of textile coatings and / or textile finishing agents.
Citation Information
Patent Citations
Styrene-butadiene latex for fabric coating and preparation method of styrene-butadiene latex
CN106749917A
Styrene-butadiene latex for textile coatings and preparation method of styrene-butadiene latex
CN108503752A
Regenerated carboxylic butadiene-styrene latex for leather and preparation method of regenerated carboxylic butadiene-styrene latex
CN111154020A